ANALISIS VEGETASI TUMBUHAN NON BUDIDAYA ASTERACEAE BERPOTENSI PESTISIDA NABATI DI DISTRIK MERAUKE DAN SEMANGGA - La Hisa; Albert Wilil; Amelia Agustina Limbongan; Nova Suryawati Monika; Nurhening Yuni Ekowati (Universitas Musamus, Merauke, Papua, 2017)
Wild plants vegetation in Merauke area as the main ingredient of botanical pesticides showed that utilization of organism considered as unuseful even as weeds can be utilized as pesticides. Asteraceae is one of the families that has species with antimicrobe contents which potential for botanical pesticides. The study was held in Merauke, and Semangga Districts from August to November 2016. The research method is quantitative. The identification used non-destructive measures, based on plant organism reviews taxonomically. Determination of sample plots used quadrat sampling technique with vegetation analysis. The result showed 16 species of wild plants in the Asteraceae family which have potential as botanical pesticides in Merauke regency. The dominant species with the highest density, frequency of attendance and leaf canopy closure are the species which have high possibility to utilize as botanical pesticides. They are Bidens pilosa dan Vernonia cinerea in Merauke district, with Summed Dominance Ratio sequentially 0,341 and 0,189. Ageratum conyzoides dan Vernonia cinerea in Semangga district dengan Summed Dominance Ratio sequentially 0,236 dan 0,202.